6 Pre-clinical pharmacodynamic biomarker assays of immune modulation can translate to inform exploratory endpoints of target engagement in first-in-human clinical trial stages of drug discovery. (9th November 2020) - Garland, Russell; Kirkham, Christopher; Yap, Michelle; Brackenbury, Louise; Iannitti, Tommaso; Nunan, Robert; Jenkinson, S
Abstract : Background: Lack of efficacy is a common cause of failure in Phase I and Phase II clinical trials. Pharmacodynamic (PD) biomarker assays can demonstrate target engagement and proof of mechanism; both key components to improve trial success. Biomarkers established at the pre-clinical phase can serve as exploratory endpoints in early phase clinical trials, to confirm the mode of action of the therapeutic. We show examples of human in vitro assays and murine T cell adoptive transfer models, which can be used to establish potential PD biomarkers for inclusion in the clinical phases. Methods: Human peripheral blood mononuclear cell (PBMC) were incubated with SEB in the presence of Pembrolizumab or Ipilimumab. IL-2 and IFNgamma levels were quantified by Luminex. To identify biomarkers of checkpoint inhibition, mice transferred with a defined population of ovalbumin (OVA)-specific T cells were challenged with OVA antigen or EG7 tumour. Activation and proliferation of antigen-specific T cells was determined and Nanostring gene expression analysis performed. Flow cytometry staining panels for human immune markers including CD4, CD14, CD25 and FOXP3 were established pre-clinically. As part of the assay validation process for a clinical trial, whole blood SEB activation was performed in normal donors, with Luminex analysis of IL-2, IL-17, IFNgamma and TNFalpha. Results: Immune checkpoint inhibitors resulted in increased IL-2 and IFNgamma secretion in human PBMC stimulated with SEB. In the murine PD model, anti-PD-L1 caused upregulation of CD25, IFNgamma and granzyme B by antigen-specific CD8 T cells. Gene expression analysis of murine tumours elucidated changes in response to a vaccine. Flow cytometry panel staining determined the frequencies of human Treg and monocytes, which are common targets of immune-modulating therapies. Fit-for-purpose validation was performed for a human SEB activation assay resulting in robust changes in cytokine production. Conclusions: The experiments here show the flow of experiments that can be performed to identify a PD biomarker for use in first in man trials; the pre-clinical human PBMC SEB screening assay provides a simple assay demonstrating that a therapy can enhance T cell function and would be translatable to the clinic. The murine PD model provides a platform to screen for biomarkers of T cell function and monitor gene expression modulation. Biomarkers identified in the murine setting provide a good starting point for exploratory assessment in early phase clinical trials, where inclusion of exploratory PD biomarker endpoints in can confirm proof of mechanism and improve study success rates. Ethics Approval: Human tissues used in this study were collected with ethical approval from UK Research Ethics Committee South West, Bristol (UK), approval number 15/SW/0029.